NILAI PENDIDIKAN MORAL RELIGIUS DALAM PUISI LAGU IBUNDA KARYA ACEP ZAMZAM NOOR - Age Januar; Ria Supriati; Elfa Indrian; Tina Nursakinah (CV. Kalimasada Group, 2026)
This study aims to describe the religious moral education values contained in the poem Lagu Ibunda by Acep Zamzam Noor and their relevance to character education. It employs a qualitative descriptive method with reading, note-taking, and content-analysis techniques. The data, in the form of the poem's lines and stanzas, were analyzed using a moral-value framework that classifies human moral relations into three categories: the relationship between humans and God, with oneself, and with others (Nurgiyantoro, 2013). The findings reveal three categories of religious moral values. First, the human-God relationship is manifested through faith, obedience, and worship. Second, the relationship with oneself appears in the values of patience and sincerity. Third, the relationship with others is reflected in devotion to parents and mutual help in goodness. These values are relevant as materials for literature learning and the strengthening of character education in schools. This study confirms that poetry can serve as a medium for internalizing religious moral values for students.